Quranic Deliberation Between the Different Buildings Applied Phonemic and Semantic Study (Raparin Journal of Humanities (RJH), 2022)
This study investigates phonetic, structural and lexical heterogeneities in the heterogeneous words in similar verses in the Holy Qur’an in search of phonetic and structural heterogeneity. And the nature of their voices and qualities and strength.Perhaps what distinguished this study from its predecessors is that it is an applied and analytical audio study in which we used modern methods and new techniques, as it is not satisfied with the structural correspondence of written vocabulary, but goes beyond that to the use of vocabulary sounds, melodies, echoes, and rhythm through (QRbarcod), so if the reader wants He was able to access the sounds and melodies of the vocabulary through his smart phone easily and in a short time. The ideas and opinions presented and the results we reached are based on old and new sources, links in YouTube and illustrations.